Gastos públicos e desenvolvimento sócio-econômico: o caso dos Municípios Do Piauí - Araújo, Valmir Barbosa de (2008)
Measuring the impact of the public expenses on the well-being level, which stands through the Human Development Index (HDI) and the Poverty Index (POVI, constitutes the central focus of this work, which will take the state of Piauí as reference. This has been a hypothesis tested in relevant international empirical works of the literature, initiated by Aschauer (1989) and intensely tested by Barro (1990; 1991), from where arose the term "Barro’s Regressions" due to their importance, and in Brazil, Ferreira (1994) began the empirical testing. Official data base from the National Treasury regarding public expenses with health, education, housing and welfare of 219 municipalities gave support to the analysis in order to test whether or not these expenses provokes well-being increase and reduces the social inequalities of the population. For doing this, an econometric modeling has been built up through which it could be inferred, with reliable statistical significance, that the effect of the expenses with health, education, housing and welfare on the HDI is positive, and the more developed is the municipality the greater is such an effect. On the other hand, in spite of the effect of the expenses on the POVI being as well as positive, its magnitude is inversely related to the development stage of the municipality.